Artificial defoliation during budding stage in sunflower - Silva, Paulo Regis F. da; Fleck, Nilson G.; Heckler, João C. (Pesquisa Agropecuaria Brasileira, 2014)
In order to quantify reductions in leaf area which can be tolerated by sunflower plants (Helianthus annuus L.), an experiment was carried out at the Estação Experimental Agronômica of Universidade Federal do Rio Grande do Sul, in Guaíba, RS, Brazil, during the 1982/83 growing season. Plants were defoliated in two dates during the budding stage: when inflorescence head was visible, but tightly surrounded by young leaves, and when inflorescence began to open, with ray florets visible. In each of those dates eight defoliation levels were applied: removal of the leaves of the upper, medium and lower thirds of plant, individually; combination of these levels two by two; removal of all leaves, and an undefoliated check. There were no signiticant differences between defoliation dates for grain yield, grain weight, grain number in heads and head diameter. However, plant height, dry weight of stem plus head, and leaf area index varied with defoliation dates. Ali defoliation levels decreased grain yield in relation to check, with reductions varying from 16 to 100%, except for treatments where leaves were removed from the lower third of the plant and from the medium third. The levels of leaf removal affected statistically all characteristics evaluated.
Keywords: Helianthus annuus L.; Conti-GH 7811 cultivar